Reasons for not receiving thrombolytic therapy in patients with acute myocardial infarction admitted to Bu-Ali Sina Hospital in Qazvin (2013-14) - MM. Daei; M. Karimi Rad; M. Khalaja (The Journal of Qazvin University of Medical Sciences, 2017)
This hospital-based cross-sectional study was conducted in 2013-14 in Qazvin Bu-Ali Sina Hospital. 170 patients with acute myocardial infarction who not receiving thrombolytic therapy entered the study and were analyzed. Medical history, physical examination, twelve lead ECG and cardiac biomarkers were obtained. The mean age of the patients was 63.4±14.4 years (from 19 to 90 years). 110 (64.7%) of the patients were male and 48 (28.2%) were diabetic. 86 (50%) of patients due to late presentation and 47 (28%) due to lack of diagnosis and 29 (17%) due to contraindication and 8 (5%) due to autolysis or coronary spam were not received thrombolytic therapy. We could reduce failure of receiving thrombolytic therapy more than seventy five percent with increasing people's awareness about the symptoms of myocardial infarction and skills of health staff in relation to the proper and timely diagnosis of myocardial infarction.